2014
DOI: 10.1007/s10555-014-9498-0
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and cancer: a casual or causal relationship: revisited

Abstract: Human platelets arise as subcellular fragments of megakaryocytes in bone marrow. The physiologic demand, presence of disease such as cancer, or drug effects can regulate the production circulating platelets. Platelet biology is essential to hemostasis, vascular integrity, angiogenesis, inflammation, innate immunity, wound healing, and cancer biology. The most critical biological platelet response is serving as “First Responders” during the wounding process. The exposure of extracellular matrix proteins and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
262
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(282 citation statements)
references
References 457 publications
1
262
0
19
Order By: Relevance
“…This is consistent to the finding of CD34 expression in mature-appearing megakaryocytes in reactive and disorders of bone marrows (40), and increased ploidization of megakaryocytes has been reported in patients with metastatic tumors (43). Platelets, which are released from megakaryocytes in bone marrow, have recently been recognized to play an important role in cancer metastasis (44,45), and the gene expression profile of platelets has been shown to efficiently distinguish individuals with or without cancers (46). Platelet counts have also been investigated for cancer prognosis, and the data are still in conflict (47).…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent to the finding of CD34 expression in mature-appearing megakaryocytes in reactive and disorders of bone marrows (40), and increased ploidization of megakaryocytes has been reported in patients with metastatic tumors (43). Platelets, which are released from megakaryocytes in bone marrow, have recently been recognized to play an important role in cancer metastasis (44,45), and the gene expression profile of platelets has been shown to efficiently distinguish individuals with or without cancers (46). Platelet counts have also been investigated for cancer prognosis, and the data are still in conflict (47).…”
Section: Discussionsupporting
confidence: 88%
“…The elevation of platelets could promote the metastatic potential of tumor cells through several pathways 21. Platelets have been reported to promote the development and enlargement of tumors by non‐inflammatory mechanisms, including stimulation of MM9 synthesis and production of adhesive molecules and growth factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been observed that platelets interact with malignant cells and suppress the inflammatory response against them. In addition, platelets secrete various growth factors and cytokines that promote angiogenesis, tumor growth, invasion and metastasis either directly or indirectly (4)(5)(6). Several clinical studies (7-10) have aimed to evaluate whether these interactions between white blood cells and platelets on one side and tumor cells on the other side may cause measurable alterations in blood parameters, as they are depicted in the complete blood count test.…”
Section: Discussionmentioning
confidence: 99%
“…White blood cells are key mediators in this response (2), in addition to platelets, which are involved in mechanisms promoting tumor growth and metastasis (4)(5)(6). Various white blood cell and platelet indices, including neutrophil-to-lymphocyte ratio, platelet count, mean platelet volume and platelet-to-lymphocyte ratio, have been reported as potential markers for predicting the progression or recurrence of disease and/or overall survival in several forms of cancer (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%